2016
DOI: 10.1038/srep35203
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain Gene Screening Identifies a New Mesoaccumbal Glutamatergic Pathway and a Marker for Dopamine Cells Neuroprotected in Parkinson’s Disease

Abstract: The ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) of the midbrain are associated with Parkinson’s disease (PD), schizophrenia, mood disorders and addiction. Based on the recently unraveled heterogeneity within the VTA and SNc, where glutamate, GABA and co-releasing neurons have been found to co-exist with the classical dopamine neurons, there is a compelling need for identification of gene expression patterns that represent this heterogeneity and that are of value for development of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 71 publications
13
63
0
Order By: Relevance
“…Nurr1 null mice die within 24h after birth and conditional knockout of Nr4a2 in DA neurons in adult animals caused decreased expression of DA markers, including Th and Slc6a3 (DAT), followed by progressive loss of DA (Castillo et al 1998;Kadkhodaei et al 2009Kadkhodaei et al , 2013 (Chang et al 2019;Lindefors and Ungerstedt 1990;Rodríguez-Puertas et al 1999). There are additional levels of crosstalk between glutamate and dopamine-glutamate neurons and their local synapses within the midbrain DA regions (Dobi et al 2010;Morales and Root 2014;Viereckel et al 2016;Wang and Morales 2009;Yamaguchi et al 2015). In our study we detect increased levels of metabotropic glutamate receptor 1 and ionotropic glutamate receptor NMDA 3A.…”
Section: Vta and Snc Transcriptomes Respond Distinctly To Da Deficiencysupporting
confidence: 50%
“…Nurr1 null mice die within 24h after birth and conditional knockout of Nr4a2 in DA neurons in adult animals caused decreased expression of DA markers, including Th and Slc6a3 (DAT), followed by progressive loss of DA (Castillo et al 1998;Kadkhodaei et al 2009Kadkhodaei et al , 2013 (Chang et al 2019;Lindefors and Ungerstedt 1990;Rodríguez-Puertas et al 1999). There are additional levels of crosstalk between glutamate and dopamine-glutamate neurons and their local synapses within the midbrain DA regions (Dobi et al 2010;Morales and Root 2014;Viereckel et al 2016;Wang and Morales 2009;Yamaguchi et al 2015). In our study we detect increased levels of metabotropic glutamate receptor 1 and ionotropic glutamate receptor NMDA 3A.…”
Section: Vta and Snc Transcriptomes Respond Distinctly To Da Deficiencysupporting
confidence: 50%
“…47,50 In addition, we identified four P7 MB DA subset clusters ( Figure 2D). Marker gene analysis confirmed that three of the clusters correspond to DA neurons from the VTA (Otx2 and Neurod6; P7.MB.1), 51,52 the periaqueductal gray area (PAG; Vip and Pnoc; P7.MB.3), 53,54 and the SN (Sox6, Aldh1a7, Ndnf, Serpine2, Rbp4, and Fgf20; P7.MB.4) 38,51,55,56 (Tables 1, S2, and S3). These data are consistent with recent scRNA-seq studies of similar populations.…”
Section: Scrna-seq Reveals Biologically and Temporally Discriminatingmentioning
confidence: 82%
“…) and we have recently reported the possibility to record glutamate release in the nucleus accumbens following optogenetic stimulation (Viereckel et al . ; Wang et al . ).…”
Section: Discussionmentioning
confidence: 99%